Dimensionamento de uma peneira aplicada a indústria salineira - Mendes, Natanael Expedito de Carvalho (Universidade Federal Rural do Semi-Árido, 2020)
Vibrating screens are present in several industrial sectors, being one of the main operations of a production line. The separation of elements in terms of their granulometry is essential in the salt production process, since it is classified according to its granulometry. Salt is one of the main industrial branches of the state of Rio Grande do Norte, which is the largest Brazilian salt producer, and Brazil occupies the fifth place in the world ranking. In this work, the sieve material was defined as well as the sizing of the structural elements of the sieve, as well as the sieving surface, the rotation speed and selection of the drives were carried out. In general, the work brings a proposal for a sieve applied to the salt sector for the production of ground salt.
Keywords: Sal; peneira vibratória.; sal moído; peneiramento industrial; ENGENHARIAS::ENGENHARIA MECANICA